SEM Observations on the Mechanism of Platelet Release from Megakaryocytes - Djaldetti, Meir; Fishman, Pnina; Bessler, Hanna; Notti, Ida (Thrombosis and Haemostasis, 1979)
Normal human bone marrow megakaryocytes were examined with the scanning electron microscope (SEM) to clarify the mechanism of platelet release. Several types of megakaryocytes were detected according to their surface appearance, i. e. with wrinkles, ridges, villous formations, round blebs and cells with platelets still attached to the cell membrane. These observations are consistent with the concept that bleb formation is at least one of the mechanisms for platelet liberation.